Groundwater quality assessment of Domiz refugee camp in Duhok governorate, Kurdistan region, Iraq. - Nabaz I. Mohammed; Karzan A. Abduljabar; Honar S. Mahdi; Hojeen M. Abdullah; Sami Youssef (Zanco Journal of Pure and Applied Sciences, 2020)
Groundwater is considered the fundamental source of drinking uses in Domiz refugee camp, Duhok governorate. Water quality investigation is critical component for determining water consumption. A field assessment was performed on August 2019 in order to examine the groundwater quality used for the refugees in Domiz camp. Groundwater samples were collected from 8 observation wells, 5 wells inside the camp and 3 wells outside the camp limits, and water samples investigated for basic physico-chemical parameters, major elements, as well as certain toxic metals to find out the suitability of groundwater sources for drinking purposes. The analytical out comes display high concentrations of TDS, EC, TH, SO4, and NO3 ions which refers to signs of contamination. Groundwater facies via piper diagram in the study area was primarily of Ca-Mg-Na-HCO3 water type. Heavy metals show high concentration levels in some groundwater samples above drinking water permissible standard prescribed by World Health Organization. These high contents of major elements beside heavy metals in groundwater were probably due to the seepage of unprocessed waste waters from the camp. WQI method were performed to assess the current condition of groundwater samples, then the result revealed variation in water quality classes ranging from very poor to excellent water class.